Economies of scale, efficiency and profitability of the convection industry in the city of Palembang - Sandrat, Tomi; Mukhlis, Mukhlis; Apriani, Deassy (Optimum: Jurnal Ekonomi dan Pembangunan, 2024)
The development of the industrial sector is greatly influenced by economies of scale, efficiency and profitability. The small convection industrial sector always follows changes in clothing models and creativity that consumers like. This research aims to find out the value of economies of scale and measure the level of efficiency and profitability in small convection industries in the city of Palembang. The type of data used is primary data related to small convection industries in Palembang City. The research method used is qualitative and quantitative with analysis of the scale of production results using the Cobb-Douglas production function, efficiency and profitability. The research results show that the variables of labor (X1), capital (X2) and digital technology (dummy) simultaneously and partially have a positive and significant effect on the amount of production (Y). The economic scale of the small convection industry in Palembang City is in a condition where the return to scale is decreasing. The efficiency value is above average at 52 percent and below average at 48 percent. Agencies or authorities at the Palembang City level, including related parties, are expected to be more active in socializing People's Business Credit so as to facilitate capital and marketing of small convection industries, because based on the results of in-depth interviews with respondents, overall they already have business capital, and the government is expected to be able to distribute it. assistance with production support equipment to business actors thereby providing encouragement to improve production performance.